2020
DOI: 10.1039/d0dt00980f
|View full text |Cite
|
Sign up to set email alerts
|

A novel self-assembled-derived 1D MnO2@Co3O4 composite as a high-performance Li-ion storage anode material

Abstract: Manganese dioxide (MnO2) is a high-performance anodic material and applied widely in lithium-ion batteries (LIBs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…24 The tightly self-agglomerating structure decreases the active site on the surface of electrode, attenuates the lithium ion transport dynamics, and makes it difficult for lithium ions to reach the inside of the electrode. 25,26 There are two main methods to intensifies the kinetics of Li-ion diffusion in MXene self-supporting films. One is to introducing various nano material spacers such as transition metal oxides to prepare composite electrodes; the other is to modify MXene films such as preparing MXene foam.…”
Section: Introductionmentioning
confidence: 99%
“…24 The tightly self-agglomerating structure decreases the active site on the surface of electrode, attenuates the lithium ion transport dynamics, and makes it difficult for lithium ions to reach the inside of the electrode. 25,26 There are two main methods to intensifies the kinetics of Li-ion diffusion in MXene self-supporting films. One is to introducing various nano material spacers such as transition metal oxides to prepare composite electrodes; the other is to modify MXene films such as preparing MXene foam.…”
Section: Introductionmentioning
confidence: 99%
“…1J, shows four distinct concentric diffraction rings, which can be assigned to the (220), (311), ( 400) and (511) planes of Co 3 O 4 . 19 The EDS mapping showed the uniform homogeneous distribution of Co, Mn, C, O and N in the composite. The atomic ratio of Mn and Co in MnO 2 @Co 3 O 4 is around 3 : 1 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…S1 †). The tandem structure of Co 3 O 4 was observed on the surface of 19 The crystal size of the Co 3 O 4 NPs calculated using the spinel (111) plane (at 2θ = 21.98°) was 7.44 nm according to the Debye-Scherrer equation. It was found that the obtained Co 3 O 4 have abundant exposed highenergy (111) facets, which have been demonstrated to be more active than (001) crystal facets in catalysis and sensing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B presents the isotherm of CoNi/NPSC@MnO-500, which displays a typical type IV isotherm with an H3-type hysteresis loop, indicating the mesoporous characteristic of CoNi/NPSC@MnO-500. 50 The BET surface area and the average adsorption pore diameters were 16.994 m 2 g −1 and 10.046 nm. It is well known that a larger specific surface area and suitable pore size can provide more active sites in turn to improve catalytic activity.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 95%